Resultado do Obstétrico de Gravidezes Gemelares Resultantes de Fecundação in Vitro, Microinjeção e Estimulação da Ovulação em Comparação com Espontâneas - Simões, T (2012)
Introduction: Uncontrolled studies suggest that twins conceived by in vitro fertilization have increased rates of preterm birth and low birth weight and would warrant increased antenatal monitoring. The objective of this study was to compare the obstetric outcome of twin pregnancies conceived by in vitro fertilization or intracytoplasmic sperm injection (IVF/ICSI) and ovulation induction with those conceived spontaneously. Methods: All twin deliveries achieved by IVF/ICSI (n=235) and ovulation induction (n=68) from September 1994 through December 2010 were evaluated. Both groups and an additional control group who conceived spontaneously (n=997) and was delivered during the same time period were compared with each other. Results: In univariate analysis, patients who conceived with the assistance of IVF/ICSI had a significantly higher risk of being older (p=0.01), nulliparous (p=0.01), having hypertensive disorders (p=0.012), gestational diabetes mellitus (p=0.031), cesarean section (p=0.008) and lower gestational age at birth, compared with the control group. Newborns had similar birthweights in all groups (2229±544g; 2102±619g; 2251±553g). Spontaneous pregnancies had a higher risk of being monochorionic 38.4% versus 16.2% and 10.2% (p=0.01). Multivariate analysis however showed that patients who conceived with the assistance of IVF/ICSI only had a higher risk of gestational diabetes (OR=1.91,95%CI 1.168-3.120; p=0.01). Conclusions: Our study shows that twin pregnancies conceived with the assistance of IVF/ICSI had a higher risk of gestacional diabetes and a lower gestacional age at birth. Birthweights were similar, as was the incidence of perinatal death, low birth weight infants, and congenital malformations.